العقيدة والشزيعة والأخلاق: علاقتها في بناء الأمة الاءسلامية - حسيدا اواغ @ يعقوب (Universiti Sains Islam Malaysia, 2010)
The title of the research is "the Akidah, Syari'at and Akhlak: the Connection in the Muslim Nation". These three aspects are related to produce a developed Ummah. As we know, the Akidah is the basis, supported by Syari'at and completed by Akhlak. These library researches involve a number of libraries in Malaysia. This study sought to look at the task of these three aspects in the construction of the Muslim nation. The finding indicates that the success of Muslims come from the appreciation of Akhlak based on true Akidah and Syari'at. Finally, the research concludes that good Akidah gives positive impact to human development.